2020
DOI: 10.1002/bin.1754
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and treatment of escape from attention in the form of conversation

Abstract: The purpose of this study was to evaluate treatment procedures for problem behavior maintained by escape from attention in the form of conversation for a child diagnosed with autism spectrum disorder. After conducting a functional analysis that confirmed this function, we implemented a preference assessment to identify some forms of attention that were not aversive. Treatment consisted of four conditions, implemented in a series of reversals. During each condition, the participant chose from some of the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…As such, future studies should continue to explore procedures that increase the preference for social interaction in individuals whose problem behavior is maintained by escape from attention. Harper et al (2013), Hagopian et al, (2001), Tiger et al (2009), andCengher et al (2021) initiated their functional analyses using traditional test and control procedures (i.e., escape from demands, tangible, attention, and toy play). During these initial analyses, the authors observed elevated rates of problem behavior in the toy play and escape-from-demands conditions.…”
Section: F I G U R E 2 James's Functional Analysis Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As such, future studies should continue to explore procedures that increase the preference for social interaction in individuals whose problem behavior is maintained by escape from attention. Harper et al (2013), Hagopian et al, (2001), Tiger et al (2009), andCengher et al (2021) initiated their functional analyses using traditional test and control procedures (i.e., escape from demands, tangible, attention, and toy play). During these initial analyses, the authors observed elevated rates of problem behavior in the toy play and escape-from-demands conditions.…”
Section: F I G U R E 2 James's Functional Analysis Resultsmentioning
confidence: 99%
“…(2009), and Cengher et al. (2021) initiated their functional analyses using traditional test and control procedures (i.e., escape from demands, tangible, attention, and toy play). During these initial analyses, the authors observed elevated rates of problem behavior in the toy play and escape‐from‐demands conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For Khloe, we also found that a divided attention context evoked aerophagia. Other studies found that certain forms of attention can be punishing (Cengher et al., 2021b), can reduce one’s speech to the point where they are diagnosed with selective mutism (Cengher et al, 2021a), and can function as a reinforcer for extremely dangerous problematic behavior (e.g., pica, Ness et al, 2020). Collectively, these studies demonstrate that attention can play many roles.…”
Section: Recommendations To Clinicians and Studentsmentioning
confidence: 99%